Motion sensor controlled lighting - Choo, Kenneth Hui Rong (Nanyang Technological University, 2022)
Since the first invention of motion sensor in the 1940s, the technology evolves to catch up with the requirements of the consumers. There are opportunities for the pace that it is progressing at. The project has both scientific and practical goals. The scientific goals underscore the advantages of cost and ease of implementation, among other opportunities. Practically, the project raises questions about how the technology can be developed to be user friendly past the 21st century. Motion sensors are widely used and can be seen everywhere. They can often be the subject of installer frustration and the cost of incorporating such a technology for domestic use can be costly due to various settings and requirements. The project aims at finding out if the motion sensor implementation can be made more inexpensive and easily implemented. To answer this question, the project scope contains a full analysis of the prototype and its functional steps of operation. Attempts is to be made to overcome its forecasted flaws.